BARRIERS TO LEARNING MATHEMATICS IN INCLUSION CLASSROOMS: PERSPECTIVES OF DEAF STUDENTS AND TEACHERS - Afra Fadhila, Yoan; Izzatika, Anna Fi; Putranto, Sumbaji (JPI (Jurnal Pendidikan Inklusi), 2024)
This study describe teachers and students with deafblindness perceive the difficulties of learning mathematics in the inclusive classroom. The purpose of this study was to find the problems faced by both of them when learning mathematics in the inclusive classroom. This study used a descriptive qualitative approach with data collection through observation, interviews, and documentation. Two deaf students and two maths teachers who teach in the inclusive class were involved in this study. The results of the study, it can be concluded that in the learning process in the inclusion class there are obstacles that come from internal factors, in the implementation of learning, and social factors. The lack of encouragement and interest of deaf students to learn mathematics is the main obstacle for students and teachers. Meanwhile, some of the challenges faced by students include the teacher's difficulty in choosing various learning approaches, processing materials for deaf students, each of whom has a different level of ability, the lack of availability of learning media and facilities provided by the school, and the lack of special assistant teachers at school. Keywords: Learning Disabilities, Math, Inclusive Class, Deaf Student, Teacher